In shade of Olympic glory: what should we know about female athletes triad? – a review - Bielicka, Anna Maria; Bochenek, Hubert; Bzoma, Michał; Gugulska, Julia; Czerepak, Irmina (Journal of Education, Health and Sport, 2024)
introduction and purpose: The numerous advantages of sport are widely known. Millions of children worldwide are encouraged to start training and significant part of them decide to start professional training. However, there are also certain health risk connected with intensive physical activity. One of them is female athletes triad – a syndrome consisting of three components: low energy availability (LEA), dysregulation of menstrual cycle and impaired bone mineral density (BMD). description of the state of knowledge: The intensive physical activity, especially in adolescent women may have deleterious influence on their health and, in consequence, on further sports career. Female athletes triad often co-occurs with eating disorders, especially in sports where slim shape is desirable. Inadequate energy availability results in menstrual cycle dysfunction, meanwhile insufficient level of female sex hormones (estrogens) is detrimental for bones health leading to frequent injuries and stress fractures. In result the vicious cycle of female athletes triad is closed and general condition of athlete deteriorates. summary: This paper aims to briefly review current state of knowledge on female athletes triad. It is vital to raise awareness of female athlete triad symptoms among medical professionals as well as sportswomen and members of coaching team to facilitate early diagnosis and proper treatment to avoid further complications.